Development of a Mass-Gathering Triage Tool: An Australian Perspective. Issue 1 (8th December 2016) - Cannon, Matt; Roitman, Rebecca; Ranse, Jamie; Morphet, Julia
Abstract: Many health service organizations deploy first responders and health care professionals to mass gatherings to assess and manage injuries and illnesses. Patient presentation rates (PPRs) to on-site health services at a mass gathering range from 0.48-170 per 10, 000 participants. Transport to hospital rates (TTHRs) range from 0.035-15 per 10, 000 participants. The aim of this report was to outline the current literature pertaining to mass-gathering triage and to describe the development of a mass-gathering triage tool for use in the Australian context by first responders. The tool is based on the principles of triage, previous mass-gathering triage tools, existing Australian triage systems, and Australian contextual considerations. The model is designed to be appropriate for use by first responders. M Cannon, R Roitman, J Ranse, J Morphet .Development of a mass-gathering triage tool: an Australian perspective .Prehosp Disaster Med .2017 ;32 (1 ):101 –105 .